The relationship between anaesthetic technique, clinicopathological characteristics and the magnitude of the postoperative systemic inflammatory response in patients undergoing elective surgery for colon cancer - Alhayyan, Aliah M. (PLoS One, 2020)
BACKGROUND/AIM: The magnitude of the postoperative systemic inflammatory response (SIR) is now recognised to be associated with both short and long-term outcomes in patients undergoing surgery for colon cancer. During such surgery, it is unclear whether the anaesthetic regimens influence the magnitude of the postoperative SIR, independent of other factors. The aim of the present study was to examine the association between anaesthetic agents, clinicopathological characteristics and the magnitude of the postoperative SIR in patients undergoing elective surgery for colon cancer. METHODS: Patients with colon cancer who underwent elective open or laparoscopic surgery between 2008 and 2016 (n = 409) were studied at a single center. The relationship between type of anaesthesia, surgical technique; open (n = 241) versus laparoscopic (n = 168) and clinicopathological characteristics was examined by using chi-square testing. The chi-square test was used to determine which anaesthetic group influences the POD 2 CRP for only patients undergoing elective open colon surgery. RESULTS: The majority of patients were <75 years old, male, normal weight or obese, underwent open surgery and had regional anaesthesia, in particular an epidural approach. There was a significant association between type of anaesthesia and post-operative CRP on day 2 (p <0.001) in patients undergoing open surgery but not laparoscopic surgery. Other factors associated with type of anaesthesia included; year of operation (p <0.01), surgical technique (p <0.001), and preoperative dexamethasone (p <0.01). CONCLUSION: In patients undergoing surgery for elective colon cancer, the type of anaesthesia varied over time. The type of anaesthesia appears to influence the magnitude of the postoperative SIR on post-operative day 2 in open surgery but not laparoscopic surgery. Future work using prospective study design is required to better define this relationship.